Identifikasi Sektor Unggulan pada Sektor Ekonomi Provinsi Jawa Barat melalui Analisis Input Output - Raihani Himati Kamilah; Teti Sofia Yanti (Bandung Conference Series: Statistics, 2023)
Abstract. Input output analysis can be used to analyze inter-sector linkages and relationships in the economy of a region. In this analysis, the data presented is in the form of tables which are referred to as input output tables. This table is very important to see the economic performance of a region by looking at the linkages between economic sectors in a region both backward and forward linkages. However, only knowing how the inter-sectoral linkages are is not enough to develop an economy. Therefore, it is necessary to carry out further analysis to determine which sectors are the leading sectors. West Java Province has had an average positive economic growth for the last six years and is also the third province that has the highest GRDP in Indonesia in 2021. This research will look at how the inter-sectoral relations of the West Java economy and what are the leading sectors in West Java using input output analysis. There are three analyzes used, namely backward linkage, forward linkage, and overlay analysis. The manufacturing industry is the leading sector in West Java Province, it is also the sector that has the greatest forward and backward linkages besides the electricity and gas procurement sector. In addition, the water supply, waste management, waste and recycling sectors have the potential to become leading sectors in West Java Province. Abstrak. Analisis input output dapat digunakan dalam menganalisis keterkaitan serta hubungan antarsektor dalam perekonomian suatu wilayah. Dalam analisis ini, data yang disajikan berbentuk tabel yang disebut sebagai tabel input output. Tabel ini sangat penting untuk melihat performa perekonomian suatu wilayah dengan melihat keterkaitan antarsektor perekenomian pada suatu wilayah baik keterkaitan ke belakang maupun ke depan. Namun, hanya dengan mengetahui bagaimana keterkaitan antarsektor saja belum cukup untuk mengembangkan suatu perekonomian. Maka dari itu, perlu dilakukan analisis lebih lanjut untuk menentukan sektor mana saja yang merupakan sektor unggulan. Provinsi Jawa Barat memiliki rata-rata pertumbuhan ekonomi yang positif selama enam tahun terakhir dan juga merupakan provinsi ketiga yang memiliki PDRB tertinggi di Indonesia pada tahun 2021. Dalam penelitian ini akan dilihat bagaimana keterkaitan antarsektor perekenomian Jawa Barat dan apa saja sektor unggulan di Jawa Barat menggunakan analisis input output. Terdapat tiga analisis yang digunakan yaitu keterkaitan ke belakang, keterkaitan ke depan, dan analisis overlay. Industri pengolahan merupakan sektor unggulan Provinsi Jawa Barat, juga termasuk sektor yang memiliki nilai keterkaitan ke depan dan ke belakang yang paling besar selain sektor pengadaan listrik dan gas. Selain itu sektor pengadaan air, pengelolaan sampah, limbah dan daur ulang memiliki potensi untuk menjadi sektor unggulan di Provinsi Jawa Barat.